The Influence Of Price, Design, Feature And Brand Image On Repurchase Intention Of Wardah Foundation Products In Bandung City - Nursania, Tiara; Komara, Esi Fitriani (UNIVERSITAS PAKUAN, 2020)
This research aims to analyze the influence of price, design, feature, and brand image on repurchase intention of Wardah foundation products in the city of Bandung. The data collection technique used was non-probability sampling with purposive sampling research involving 100 female respondents who had purchased and used Wardah foundation products in Bandung, aged 17 years old. The research instrument has undergone validity and reliability testing, classical assumption testing, and multiple regression analysis using SPSS version 26. The results of this study indicate that price has a positive influence on repurchase intention, design has a positive influence on repurchase intention, feature have a positive influence on repurchase intention, and brand image has a positive influence on repurchase intention. Furthermore, price, design, features, and brand image collectively have a significant influence on repurchase intention.